Application of inorganic metal oxide nanoparticles in dairy products: Opportunities and challenges - Sabikhi, Latha; C.T., Manoj Kumar (Indian Journal of Dairy Science, 2018)
Dairy products are highly perishable in nature as they get contaminated easily with spoilage causing and pathogenic microorganisms. Dairy industries suffer huge economical losses due to the post processing contamination of dairy products. The search for new methods of food preservation is, therefore, a continuous process. Application of engineered nanomaterials as an antimicrobial agent is gaining importance in food preservation. Metal oxides in nano size exhibit strong bacteriostatic/bactericidal activity over a wide range of microorganisms. Addition of metal oxides not only improves the shelf life, but also aids in mineral enrichment of dairy products. Hence, there is a huge scope to use metal oxide nanoparticles for preservation of dairy products. This article discusses the application and scope of ZnO, MgO and CaO nanoparticles in dairy products. In addition, the key challenges that the quality and safety of the products may face owing to their addition are also discussed.